Letter from the editor (2016)
The Earth Sciences Research Journal volume 20, number 3, with eight high-quality scientific articles, is now available online for all our readers, all the related scientific community.  The publishing committee has decided to increase to four the numbers issued per year starting 2016. That will be just possible with your support.This time we want to call the attention to the necessary balance between good judgment and environmentalism.Just for a different way of thinking about environment and management resources, some self-proclaimed environmentalists take a right for pointing out, for blocking those aimed at development or exploiting resources. Their origin is located in Germany during the 60's with the Vorsorgeprinzip, or the Precautionary Principle. Green activists depict themselves as victims of economic empires of Government's neglected policies to turn into persecutors over development, competitivity, and innovation plans. As it was recently stated by the Social Issues Research Centre, this principle poses of a harmless policy. Is not our right to be protected when the unscrupulous science is applied, especially when the environment and our lives are at risk? But the use of the principle goes beyond the protection of known or foreseen risks. This principle has been recalled to block plans with just little risks - which will be balanced out thanks to the reached advantages. The precautionary doctrine is claimed whenever the little risk perception appears, no matter if the actions to take are necessary to allow future benefits.Thousands of cases around the world would be checked. Not only in mining or petroleum exploitation but genetically modified food, technology gadgets, fracking. This principle is a serious obstacle for the rational analysis. If the risk can not be demonstrated, the Vorsorgeprinzip is baseless.The science works assuming the hypothesis can not be probed, but refuted. The evidence and probes are provided to the scientific community, and they will proceed under logic and rational methods; usually, the Precautionary Principle is not an important matter at this stage of the process. But is there when that policy can turn into dangerous. It origins a fanatism, close to a religious belief. The senseless debate shows a society with a limited future, without options. All the progress is neglected for standing up at the "safe place." Our present has been just possible thanks to the bold decisions by some people with the enough vision to calculate the risks by the advantages. The trip to the Moon and the Sun System study, development of communications and treatment to sicknesses have been no possible under the precautionary principle.Our scientific community should pick the good judgment up to allow all the small steps for humanity.